Post-collisional denudation of an orogenic belt traced from geochronological and bulk-rock geochemical records of the western Korean Peninsula. Issue 1 (2nd January 2021) - Lee, Hyojong; Park, Seung-Ik; Choi, Taejin; Sim, Min Sub
ABSTRACT: The western Korean Peninsula preserves evidence for multiple Proterozoic to Phanerozoic orogenic processes along the convergent continental margins. After the Late Palaeozoic to Early Mesozoic collisional stage within the long-lived tectonic Wilson cycles, the area underwent post-collisional extensional tectonics, creating the Late Triassic to Early Jurassic basins on top of the collisional orogenic belt. Here, we present the LA-MC-ICP-MS U-Pb ages of detrital zircons and bulk-rock geochemical data from post-collisional basin fills (viz., the Nampo and Gimpo groups and the Seokmun Formation) and the overlying volcano-sedimentary sequence (Oseosan Volcanic Complex). Our results suggest that (1) the Nampo Group was supplied with detritus mainly from nearby felsic igneous rocks or geochemically equivalent migmatitic basement gneisses, while the Gimpo Group and Seokmun Formation were predominantly sourced from (meta-)sedimentary rocks, likely reflecting their structural positions in the orogenic belt in terms of the exhumed basement-dominant hinterland side vs. the cover rock-dominant foreland side of the mountain belt; (2) the ages of the youngest zircon group in the Nampo Group and the overlying Oseosan Volcanic Complex (ca. 1854 age peak in the lowermost unit and ca. 164 Ma age peak in the uppermost unit) tend to approach the sedimentation ages with ascending stratigraphic order, indicating a transition from a collisional to a convergent tectonic setting during sedimentation. The results from this study provides important insights into the sedimentary response to the evolution of the collisional orogenic belt along the western Korean Peninsula and elucidates the Mesozoic tectonic transition from collisional (closure of the Paleo-Tethys Ocean) to convergent (subduction of the Paleo-Pacific Ocean) processes in the Far East Asian continental margin.